High-Speed Imaging in Noncontact Atomic Force Microscopy - Balantekin, Müjdat; Balantekin, Müjdat (CRC Press, 2013)
We analyze the high-speed operating method that we recently developed to be used in noncontact atomic force microscopes (AFM). We simulated the method on various samples and it is shown that the method can minimize the time spent for noncontact AFM imaging experiments. The initial simulation results showed that even with an ordinary AFM cantilever imaging speeds faster than 10 frames/second can be achieved.
Nanotechnology 2013: Advanced Materials, CNTs, Particles, Films and Composites - 2013 NSTI Nanotechnology Conference and Expo, NSTI-Nanotech 2013; Washington, DC; United States; 12 May 2013 through 16 May 2013
Keywords: Atomic force microscope; Eigenmode of a cantilever; High-speed AFM imaging; Noncontact mode